Fostering success through cultural fusion: an autoethnography exploring Ọmọlúàbí-inspired interventions for marginalized K-5 students - BankOkoya, Adesuwa Wuraola (My University, 2026)
The purpose of this autoethnographic study is to explore and reflect on my personal experiences with early intervention for marginalized students within the broader social, cultural, and institutional contexts of elementary education. By grounding this exploration in the Yoruba cultural concept of Ọmọlúàbí, I examined how these interventions can empower students and facilitate their pathways to success while considering the unique challenges they face. This study sought to provide insights into the experiences with tailored support systems and underscores the importance of Yoruba cultural understanding in promoting educational equity. It elucidates the ways in which individuals navigate the complexities associated with cultural identity amidst a rapidly transforming global landscape, showcasing the enduring relevance and adaptability of these traditions. By situating personal experiences within broader historical and sociocultural frameworks, the study sought to highlight the resilience inherent in Yoruba customs and the critical significance of cultural preservation. It advocates for a reconnection with ancestral practices, thereby fostering a deeper comprehension of both individual and communal identities. This methodological approach significantly contributes to the ongoing discourse surrounding cultural continuity and revitalization, providing valuable insights into how we can honor and sustain our cultural heritage.
Keywords: Ọmọlúàbí philosophy; Marginalization in education; Equity in education; Cultural awareness in schools